Assessing the readiness of Occupational Safety and Health education implementation among hospitality higher education providers / Nur Farah Liyana Mohd Akhir and Nurshamshida Md Shamsudin - Mohd Akhir, Nur Farah Liyana; Md Shamsudin, Nurshamshida (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
Occupational safety and health have been introduced in our country started in 1994 and had been implemented in every sector. But this occupational safety and health not yet had been introduced in the education lines in our country. For other countries, some of the school have been implemented the occupational safety and health education. Occupational safety and health in the workplace are important, and it was the major concern to the employee because it will help to reduce the number of injuries and fatal cases. The implementation of OSH in academic, especially in the hospitality industry is still lacking and need to be improved. The purpose of the study is to know the readiness of occupational safety and health education implementation among hospitality higher education providers.